1987
DOI: 10.7863/jum.1987.6.8.441
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of the hand and foot in foreign body detection.

Abstract: To evaluate the possibility that sonography might be effective in the clinical detection of foreign bodies in the soft tissues, we used high‐resolution sonography to study 10 patients with suspected foreign bodies in the hand and foot. Using ultrasound, we detected foreign bodies (glass, metal wire) in the sole of the foot of two patients and glass in the hand of another. Seven patients were proved to be free of foreign bodies. In an experimental model to ascertain which types of foreign bodies could be detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Intraoperative use of ultrasonography has in fact been recommended in literature also as an aid in real-time localization of foreign bodies (31). This accurate localization enables surgeons to make smaller and cosmetically appealing incisions and remove foreign bodies with a minimum amount of dissection and operation time (33). …”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative use of ultrasonography has in fact been recommended in literature also as an aid in real-time localization of foreign bodies (31). This accurate localization enables surgeons to make smaller and cosmetically appealing incisions and remove foreign bodies with a minimum amount of dissection and operation time (33). …”
Section: Discussionmentioning
confidence: 99%
“…While the use of ultrasound is well established in evaluating foreign bodies in the extremities [17], the initial "false negative" result was likely related to the depth of the glass fragment from the skin puncture wound. The non-visualization of the pseudoaneurysm on this initial ultrasound, may be attributable to the evolving nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Gooding et al 15 inserted foreign bodies (wood, glass and metal) into the flesh of a chicken breast, and reported that ultrasound evaluation identified the foreign bodies, and also localised the depth of the object. This precise identification of depth can assist surgeons to minimise invasion of tissues so that tissue damage, blood loss and complication risks are reduced.…”
Section: Foreign Body Detectionmentioning
confidence: 99%